Profile of High School Students' Arguments on Environmental Pollution Materials in the Covid-19 Era - Yeni Puspitasari; Sri Widoretno; Joko Ariyanto; Bowo Sugiharto; Sri Dwiastuti; Candra Adi Prabowo (STAI Hubbulwathan Duri, 2022)
The study aims to identify the argumentation profile of high school students in learning in the covid-19 era. This research is quantitative descriptive with a survey method. The research population was 172 students, with a sample of 72 students. Determination of the sample using cluster random sampling technique has a balanced quality from the results of the paired F test. The research procedure was carried out by collecting data on student answers from argumentative essay questions distributed via a google form. Argumentative questions based on TAP contain six components, namely Evidence (E), Warrant (W), Backing (B), Qualifier (Q), Rebuttal (R), and Claim (C). The argumentation scoring rubric is calculated based on the Patton-Pickle rule. Data analysis was carried out by interpreting the scores obtained by students on each argumentation component that showed the argumentation profile. Most of the students' argumentation profiles, according to their components, are in the very low category scores, namely 0.5 and 1. A score of 0.5 is obtained by comparing the percentages of students: E: E: W: W: B: Q: R: C: C: C by 23.61%: 1.39%: 0.00%: 52.78%: 45.83%: 83.33 %: 4.17%: 2.78%: 2.78%: 0.00% while the score of 1 is 41.67%: 55.56%: 83.33%: 47.22%: 54.17%: 8.33%: 75.00%: 83.33%: 79.17%: 98 ,61%. Scores were obtained due to various factors, including the learning process that was less meaningful, students' understanding and reasoning of the material was not in-depth, the generalization process of evidence or theory was not appropriate.